Manajemen Peningkatan Mutu Berbasis Sekolah (MPMBS) di Daerah Perbatasan: Studi di SMP N 2 Bokan Kepulauan, Banggai Laut, Sulawesi Tengah - Trisandi Trisandi; Ahmad Afrizal Rizqi (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2019)
The implementation of School-based management in SMP N 2 Bokan Kelupauan, Kabupaten Banggai Laut Sulawesi Tengah encounters a number of problems. One of which is due to the isolated site of the school. This qualitative study describes the implementation of school based management in SMP N 2 Bokan kepulauan which is located in the outer border of Indonesia. Research data was gathered through interviews, observation, and documentation. The results showed that the implementation of the school based management in the school has not run effectively. The most significant problems that hinder the success of the implementation were incompetent human resources and the lack of society’s participation.